Positioning of aminopeptidase inhibitors in next generation cancer therapy - Hitzerd, Sarina M; Verbrugge, Sue Ellen; Ossenkoppele, Gert; Jansen, Gerrit; Peters, Godefridus J (Amino acids, 2014)
Aminopeptidases represent a class of (zinc) metalloenzymes that catalyze the cleavage of amino acids nearby the N-terminus of polypeptides, resulting in hydrolysis of peptide bonds. Aminopeptidases operate downstream of the ubiquitin–proteasome pathway and are implicated in the final step of intracellular protein degradation either by trimming proteasome-generated peptides for antigen presentation or full hydrolysis into free amino acids for recycling in renewed protein synthesis. This review focuses on the function and subcellular location of five key aminopeptidases (aminopeptidase N, leucine aminopeptidase, puromycin-sensitive aminopeptidase, leukotriene A₄hydrolase and endoplasmic reticulum aminopeptidase 1/2) and their association with different diseases, in particular cancer and their current position as target for therapeutic intervention by aminopeptidase inhibitors. Historically, bestatin was the first prototypical aminopeptidase inhibitor that entered the clinic 35 years ago and is still used for the treatment of lung cancer. More recently, new generation aminopeptidase inhibitors became available, including the aminopeptidase inhibitor prodrug tosedostat, which is currently tested in phase II clinical trials for acute myeloid leukemia. Beyond bestatin and tosedostat, medicinal chemistry has emerged with additional series of potential aminopeptidases inhibitors which are still in an early phase of (pre)clinical investigations. The expanded knowledge of the unique mechanism of action of aminopeptidases has revived interest in aminopeptidase inhibitors for drug combination regimens in anti-cancer treatment. In this context, this review will discuss relevant features and mechanisms of action of aminopeptidases and will also elaborate on factors contributing to aminopeptidase inhibitor efficacy and/or loss of efficacy due to drug resistance-related phenomena. Together, a growing body of data point to aminopeptidase inhibitors as attractive tools for combination chemotherapy, hence their implementation may be a step forward in a new era of personalized treatment of cancer patients.